Youths as promoters of rights: a learning experience in the Canton of Garabito, Costa Rica - Chan-Jiménez, Julia (2020)
This document seeks to share the process by which the “Jóvenes Promotores de Derechos” (“Youth Rights Promoters”) proposal was constructed based on a learning experience carried out with young people between ages 13 to 22 from the community of Garabito in the Central Pacific region of Costa Rica during the years 2016 and 2017.  The subject matter arises from a process of investigation, sensitization and training in Human Rights and Culture of Peace within the framework of the Proyecto Ciudades culturales: UNA alianza para el futuro (Cultural Cities Project: UNA alliance for the future), executed by academic personnel of the Vice-Rectories of Extension and of Education (Vicerectorías de Extensión y de Docencia) of the Universidad Nacional of Costa Rica (UNA) (National University of Costa Rica) in partnership with the City of Garabito’s Centro Cívico para la Paz (CCP) (Civic Center for Peace) and the City of Jaco’s Colegio Técnico Profesional (CTP) (Professional Technical High School), with participation of undergraduate and graduate students from UNA and Universidad Estatal a Distancia (UNED) (State Distance-Learning University).  The process carried out with the support of ludopedagogical tools consisted of three phases; the first, of diagnostic nature, explored young people's perceptions about the problems in their community, violence in its different expressions and the experience of Human Rights.  The second phase corresponds to the strengthening of capacities in issues of leadership, Human Rights and Culture of Peace for young people from both CCP and CTP.  The third phase corresponds to a proposal pilot provided only to 10th grade youths from CTP.  As a result, we arrive at a participatory proposal of sensitization and education aimed at young people with the objective forming them as promoters of rights in their educational centers and communities.